A fuzzy comprehensive evaluation-based node-disjoint multi-path routing for wireless sensor networks. (2018) - Gao, Teng; Song, Jin-Yan; Ding, Jin-Hua; Wang, De-Quan
How to establish node-disjoint paths is the key issue in multi-path routing of the wireless sensor networks (WSNs). In this paper, a node-disjoint multi-path protocol based on fuzzy comprehensive evaluation (MPFCE) is proposed. In the protocol, the mediate nodes selectively forwards the RREQs from the source based on the path ID and the path ability. The path ability, which is calculated based on the energy mean, the energy variance, the hop count and the retransmission number by using the fuzzy comprehensive evaluation method, reflects the energy efficiency and quality of service (QoS). Finally, the RREQ arrived at the destination contains a node-disjoint path. The simulations demonstrate that the energy consumption of MPFCE is 60-70% of HENDMR and TinyONDMR; and the transmission delay of transmitting one packet in MPFCE is about 95% of TinyONDMR and HENDMR. Moreover, the overheads used in establishing multiple paths are also less than the other protocols.